Pengelolaan Digital PR Sebagai Upaya Menjaga Citra Positif Kakak Asuh - Ridwan, Arif; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2020)
This study aims to find out how to manage digital PR utilizing instagram as an method to maintain a positive image of Yayasan Karya Kakak Asuh by adopting the POAC management concept initiated by George R. Terry. This study was carried out using a qualitative descriptive method with primary and secondary data through data collection techniques, namely in-depth interviews, observation, and documentation studies. Based on the results of research can be revealed that Yayasan Karya Kakak Asuh is in the digital management PR utilizing instagram as an method to maintain a positive image as compatible as the POAC management concept, with the following indicators: The first planning stage: conducts reserach first before planning program of activities to be implemented; second organizing stage: Yayasan Karya Kakak Asuh selects human resources as it needs by managing social media instagram; Third actuating stage: manage social media instagram with three content pillars, i.e., foster sisters and brother’s content, educational, fun and entertainment content; fourth controlling stage: observe social media instagram by viewing at instagram insights.